TOPCon, TOPCoRE or TOPCon²: A Simulation-Based Efficiency Analysis - Wöhrle, Nico; Greulich, Johannes; Richter, Armin; Wolf, Andreas; Rentsch, Jochen; Rein, Stefan (SiliconPV Conference Proceedings, 2025)
As tunnel oxide passivated contact (TOPCon) cell technology has established itself as the dominant cell technology in global photovoltaic production, this study investigates competing architectures, including TOPCoRE (TOPCon with Rear Emitter), and local TOPCon² (passivated contacts on both sample sides), to identify paths for enhancing power output by improving the cells’ front side. The authors conduct a comprehensive simulation analysis using Quokka3, with input parameters derived from internal measurements and published data. While pointing out the necessary surface parameters to achieve a certain cell efficiency evolution, the sensitivity of the cell concepts to wafer quality, base resistance, and minority carrier lifetime is evaluated. The results indicate that the TOPCoRE concept on p-type wafers can be a strong contender to the standard iTOPCon, reaching 26%+ efficiency, if equally high electrical wafer quality can be achieved. The findings highlight the importance of further optimization paths, with local Front Surface Fields or local front TOPCon layers, demonstrating potential efficiencies of up to 26.5% and more.